Age, anti-müllerian hormone, antral follicles count to predict amenorrhea or oligomenorrhea after chemotherapy with cyclophosphamide. Issue 1 (December 2015) - D'Avila, Ângela; Biolchi, Vanderlei; Capp, Edison; Corleta, Helena
Abstract Background A cohort study was performed to identify ovarian reserve markers (ORM) that predicts amenorrhea or oligomenorrhea 6 months after cyclophosphamide CTX in women with breast cancer. Methods 52 eumenorrheic patients with breast cancer were enrolled. FSH, anti-Müllerian hormone (AMH), antral follicles count (AFC) were measured before and 6 months after CTX. A logistic regression for independent samples and determination of the ROC curve were performed. Results The age of 32 years presented 96 % of sensitivity and 39 % of specificity to predict amenorrhea or oligomenorrhea with ROC area under the curve (AUC) of 0.77. ovarian reserve marker (ORM) with power to predict amenorrhea or oligomenorrhea in women after CTX were AMH <3.32 ng/mL (sensitivity of 85 %, specificity of 75 % and AUC 0.87), AFC <13 follicles (sensitivity 81 %, specificity 62 %, AUC 0.81). AMH cutoff to predict amenorrhea was 1.87 ng/mL (sensitivity 82 %, specificity 83 %, AUC 0.84) and AFC cutoff was 9 follicles (sensitivity 71 %, specificity 78 %, AUC 0.73). Conclusions ≥32-years-old women, AMH <3.32 ng/mL and AFC <13 follicles determined significantly higher risk of amenorrhea or oligomenorrhea after CTX with cyclophosphamide. The ORM age (≥32 years) analyzed together with AMH or AFC increases sensitivity and specificity in predicting amenorrhea or oligomenorrhea.